Effect of Amelogenin Solution in the Microhardness of Remineralized Enamel and Shear Bond Strength of Orthodontic Brackets - Guilherme Genovez-Júnior (Hindawi Limited, 2021)
Objectives. To evaluate the microhardness of tooth enamel remineralized with enamel matrix protein solution as well as the shear bond strength of orthodontic brackets bonded to this surface. Materials and Methods. In total, 24 human premolars were selected and divided into 3 experimental groups (n = 8): SE—sound enamel, DE—demineralized enamel, and TE—demineralized enamel treated with amelogenin solution. Samples from DE and TE groups were subjected to pH cycling to induce initial artificial caries lesion. TE group was treated with amelogenin solution. Samples were placed in artificial saliva for 7 days. Knoop microhardness was measured before any intervention (T0), after pH cycling (T1) and after amelogenin solution treatment application (T2). Twenty-four hours after ceramic orthodontic brackets were bonded, samples were subjected to shear test in a universal testing machine. Microhardness and shear measurement distributions were subjected to Kolmogorov–Smirnov normality test, which was followed by parametric tests (α = 0.05): 2-way analysis of variance (factors: enamel condition × treatment) and Tukey posttest for all three groups (SE, DE, and TE) in T0 and T2 for microhardness; analysis of variance and Tukey’s test, for shear bond strength test. Results. Means recorded for Knoop microhardness in T2, for the SE (366.7 KHN) and TE (342.8 KHN) groups, were significantly higher than those recorded for the DE group (263.5 KHN). The shear bond strength of the SE (15.44 MPa) and TE (14.84 MPa) groups statistically differed from that of the DE group (11.95 MPa). Conclusion. In vitro demineralized enamel treatment with amelogenin solution was capable of taking samples’ hardness back to levels similar to those observed for sound enamel. The shear bond strength on the enamel subjected to this treatment was similar to that observed for healthy enamel and higher than that observed for demineralized enamel.